Plasmonic silver nanoparticles for an improved VOPcPhO:P3HT organic solar cells / Khairus Syifa binti Hamdan - Khairus Syifa, Hamdan (2017)
The use of plasmon-embedded metal nanostructures enables light concentration and trapping in organic solar cells. In this work, the study was focused on the effects of surface plasmon, which incorporate organic solar cells device based on VOPcPhO:P3HT material. Several plasmonic structures have been constructed experimentally to understand the effect of optical behaviour on spherical silver particles and silver nanowires, which has been explored using finite-difference time-domain (FDTD) software. Integrating those shapes in bare silicon substrate shows enhancement in the light absorption of solar cells. The shape of metal nanostructure has been constructed experimentally like dendritic and flower-like silver structures. Three methods of fabrications have been applied to ameliorate the homogeneously silver particles in the thin film of solar cells, including electrophoretic deposition (EPD), spin coating technique, and electron beam (e-beam) evaporation technique. Field emission scanning electron microscopy (FESEM) characterization has clearly shown the specific technique that gave the best morphology. The annealing condition also has been varied for the well-formed silver nanoparticles, which was prepared by e-beam evaporation technique. The ultra-violet/visible/near-infrared (UV/VIS/NIR) spectroscopy showed that silver nanoparticles prepared by e-beam evaporation technique annealed at 250 °C has the most intense and prominent surface plasmon behaviour. Hence, the silver particles prepared at this optimum condition has been chosen to be integrated in organic solar cells device of VOPcPhO:P3HT blend system. The integrated device shows a very significant increase in efficiency and stability. The calculated efficiency from the current-voltage (I-V) measurement showed an increment from 1.09% of pristine device to 1.89% of the device with silver nanoparticles, which is the best increment of efficiency of VOPcPhO:P3HT blend organic solar cells device reported to date.